1999
DOI: 10.1016/s0014-5793(99)01028-5
|View full text |Cite
|
Sign up to set email alerts
|

β‐Amyloid fragment 25–35 selectively decreases complex IV activity in isolated mitochondria

Abstract: Defects in mitochondrial oxidative metabolism, in particular decreased activity of cytochrome c oxidase, have been demonstrated in Alzheimer's disease, and after the expression of the amyloid precursor protein (APP) in cultured cells, suggesting that mitochondria might be involved in L L-amyloid toxicity. Recent evidence suggests that the proteolysis of APP to generate L L-amyloid is at least in part intracellular, preceding the deposition of extracellular fibrils. We have therefore investigated the effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
107
1
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 182 publications
(122 citation statements)
references
References 40 publications
13
107
1
1
Order By: Relevance
“…Therefore, this peptide exhibits significant levels of molecular aggregation, retaining the toxicity of the full-length peptide, although it is lacking of metal binding sites. In line with this finding, it has been proposed that Ab (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) peptide represents the biologically active region of Ab [6,7]. However, although the deposition of Ab in the central nervous system is a hallmark of AD and a possible cause of neurodegeneration [1,8,9], several reports have suggested that some non-aggregated amyloid molecules and its peptide fragments, may intercalate into the plasma membrane and directly alter membrane activities [10,11].…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations
“…Therefore, this peptide exhibits significant levels of molecular aggregation, retaining the toxicity of the full-length peptide, although it is lacking of metal binding sites. In line with this finding, it has been proposed that Ab (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) peptide represents the biologically active region of Ab [6,7]. However, although the deposition of Ab in the central nervous system is a hallmark of AD and a possible cause of neurodegeneration [1,8,9], several reports have suggested that some non-aggregated amyloid molecules and its peptide fragments, may intercalate into the plasma membrane and directly alter membrane activities [10,11].…”
Section: Introductionmentioning
confidence: 92%
“…Previous papers have reported that programmed cell death pathways may be involved in the mechanisms responsible for AD [14,15]. On the basis of these findings, it seems particularly interesting to further investigate the mechanism of toxicity induced by the non-aggregated forms of Ab (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35), trying to evidence the existence of apoptotic events in the toxic mechanism mediated by Ab (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Once inside mitochondria, Aβ, either produced by APP processing or by direct import, could induce the RC inhibition. Canevari et al, and Casley et al, showed that nonsynaptic brain mitochondria from rats treated with a truncated form of Aβ displayed a specifically complex IV inhibition, whereas other RC complexes remained unaltered (Canevari et al, 1999;Casley et al, 2002). Moreover, Parks et al, reported Aβ-induced complex IV inhibition in rat liver isolated mitochondria (Parks et al, 2001).…”
Section: In Alzheimer´s Diseasementioning
confidence: 99%